2020
DOI: 10.1016/j.heliyon.2019.e03107
|View full text |Cite
|
Sign up to set email alerts
|

An anthropometric evaluation of the scapula, with emphasis on the coracoid process and glenoid fossa in a South African population

Abstract: The exact dimensions of the scapula, including the coracoid process and glenoid fossa, are fundamental in the patho-mechanics of the glenohumeral joint (GHJ); as these structures act as initiators of shoulder movement. The aim of the study was to evaluate the anthropometric parameters of the GHJ, with emphasis on the coracoid process and glenoid fossa. The morphometric (Linear Tools 2012, 0-150mm, LIN 86500963) and morphological parameters of a total of one hundred and sixty-four (n ¼ 164) dry bone scapulae [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…So if the weight or the body stature of the patient is unknown then it can help decide the size of glenoid fossa. Kreiehoff also worked on this topic and found that the orientation or the dimension of the glenoid cavity can be estimated by measuring the angle the glenoid cavity makes with the scapular spine [14][15] . Also one more way to calculate the dimension of the glenoid cavity is to measure the angle between glenoid cavity and lateral border and also it can be measured by finding the angle between median border and glenoid cavity.…”
Section: Discussionmentioning
confidence: 99%
“…So if the weight or the body stature of the patient is unknown then it can help decide the size of glenoid fossa. Kreiehoff also worked on this topic and found that the orientation or the dimension of the glenoid cavity can be estimated by measuring the angle the glenoid cavity makes with the scapular spine [14][15] . Also one more way to calculate the dimension of the glenoid cavity is to measure the angle between glenoid cavity and lateral border and also it can be measured by finding the angle between median border and glenoid cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have performed the morphometric analysis of cavitas glenoidalis on different materials (dry bone, fresh cadaver or 3D-CT reconstruction) in different populations [7,10,18,21,22,28]. This study is a radiological study and measurements were performed through multidetector CT.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that higher values of our study than all other researches may be associated with race Prescher and Klümpen (1997) [4] stated about the cause of such difference as loose attachment of the glenoid labrum onto the GC at notch area. In the absence of the glenoid notch, the glenoid labrum is attached along GC margins; therefore, the shoulder joint is more stable [6,7]. We reviewed GCs with notch according to the notch count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to previous studies. 3,21 The mean of the normal Indonesian glenoid inclination, which was measured using β angle, was 74.0° and the mean of the normal Indonesian glenoid version was 12.3° retroversion. 6 It was difficult to compare both the glenoid inclination and version with previous studies due to differences in measurement methods.…”
Section: Morphometrymentioning
confidence: 99%